2012
DOI: 10.1111/sode.12005
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Trust Consistency and the Quality of Peer Relationships During Childhood

Abstract: Five hundred five children (267 female) enrolled in school years 5 and 6 in the UK (M = 9 years and 9 months) completed measures of trust beliefs in peers, best friendships, ascriptions of trustworthiness, and trustworthiness toward peers. Children's social disengagement, peer preference, and peer victimization were assessed by sociometric ratings. It was found that, relative to children with consistent trust beliefs and trustworthiness, and those with inconsistent low trust beliefs and high trustworthiness, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 41 publications
(68 reference statements)
2
13
0
Order By: Relevance
“…Again these findings were consistent with expectation, and the findings of Rotenberg and Boulton (2012), that interpersonal trust consistency is important for psychosocial adjustment.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Again these findings were consistent with expectation, and the findings of Rotenberg and Boulton (2012), that interpersonal trust consistency is important for psychosocial adjustment.…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, similar to other peer behaviours (Galvan, Spatzier, & Juvonen, 2011;Kwon & Lease, 2009;Nesdale et al, 2009;Nesdale & Dalton, 2011), peer groups may have embedded interpersonal trust consistency as a normative expectation. In support of this proposition, Rotenberg and Boulton (2012) reported that 9-to 11-year-olds with low interpersonal trust consistency, expressed as high trust beliefs in peers and low peer-reported trustworthiness, reported lower quality peer relationships. Specifically, children with lower interpersonal trust consistency experienced lower peer preference, higher peer victimization, and higher social disengagement in comparison to children with higher interpersonal trust consistency expressed as similar peer trust beliefs and peer-reported trustworthiness scores.…”
Section: Young Children's Interpersonal Trust Consistency As a Predicmentioning
confidence: 90%
See 3 more Smart Citations